2007
DOI: 10.1029/2006ja011978
|View full text |Cite
|
Sign up to set email alerts
|

Cassini/Cosmic Dust Analyzer in situ dust measurements between Jupiter and Saturn

Abstract: [1] We report an analysis of the Cosmic Dust Analyzer data obtained during the interplanetary cruise of the Cassini spacecraft between Jupiter and Saturn. The data cover the time period between the Jupiter flyby and the Saturn orbit insertion. Seventeen dust particles on bound and unbound (hyperbolic) orbits were also detected, with sizes in the submicrometer to the micrometer range. Our measurements are compared with the Pioneer dust data obtained 30 years ago and model predictions. Particles on bound orbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…During its interplanetary cruise it measured interplanetary and interstellar grains (Baguhl et al 1995;Altobelli et al 2005). During the orbital tour of the Galileo mission (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) Fig.…”
Section: The Galileo Missionmentioning
confidence: 99%
See 1 more Smart Citation
“…During its interplanetary cruise it measured interplanetary and interstellar grains (Baguhl et al 1995;Altobelli et al 2005). During the orbital tour of the Galileo mission (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003) Fig.…”
Section: The Galileo Missionmentioning
confidence: 99%
“…In this way ISD particles are repeatedly recycled through the galactic evolution process (Dorschner & Henning 1995). A&A 552, A130 (2013) Direct measurements of interstellar dust were made in situ in the solar system, using the dust instruments on spacecraft like Ulysses (Grün et al 1994;Baguhl et al 1996;Landgraf et al 2000;Krüger et al 2007), Galileo (Baguhl et al 1996;Altobelli et al 2005), Helios , and Cassini (Altobelli et al 2003). Ulysses provided the most extended data set of interstellar dust in the solar system from which an ISD size distribution was derived which is valid for the Ulysses observation period and orbit .…”
Section: Introductionmentioning
confidence: 99%
“…Across different regions in the ISM, variations in extinction curves and emission/absorption features similarly suggest there may be large fluctuations in the relative abundance of large grains (Miville-Deschênes et al 2002;Gordon et al 2003;Dobashi et al 2008;Paradis et al 2009). The solar neighborhood, in particular, appears to exhibit an anomalous large-grain abundance (Krüger et al 2001;Frisch & Slavin 2003;Meisel et al 2002;Altobelli et al 2006Altobelli et al , 2007Poppe et al 2010). And Hopkins (2014b) suggested that this could explain some (but not all) of the variations in abundances observed within some star massive clusters.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Altobelli et al (2006); (2) Grün et al (1994); (3) Baguhl et al (1996); (4) Landgraf et al (2000); (5) Krüger et al (2007); (6) Baguhl et al (1996), (7) Altobelli et al (2005); (8) Altobelli et al (2003); (9) Krüger et al (2004).…”
Section: Introductionmentioning
confidence: 99%